AAA : equity valuation - Romatif, Vincent Jean-Claude Herve (2015)
This report focuses on the extent to which Switzerland tobacco market has evolved in line with changing smoking habits, dynamic competitive environment and economic developments. It analyzes the implications market realignments have had on tobacco companies and how pricing is more than ever driving growth. This equity research aims to value a Tobacco Company (Company AAA) in Switzerland and spotlights its fundamental value driver’s components and key business components. For confidentiality reasons, I have been asked to replace original company names and associated brands by pseudonyms. I have attributed surnames to each company and respective brands.